Preparation of Rice Hull-Based Activated Carbon with Ammonium Nitrate - Kilic, Ismail; Bayrak, Yuksel; Topallar, Harika; Karagoz, Buse (Asian Journal of Chemistry, 2013)
The present study deals with the preparation of rice hull-based activated carbon with ammonium nitrate. The obtained carbon was activated at temperatures between 400 and 900 ºC. The rice hull-activated carbon presented a BET surface area of 456.77 m2 g-1 and a pore volume of 0.2406 cm3 g-1 at 600 ºC. The adsorption and desorption average pore widths by BET method were found as 2.727 and 2.725 nm, respectively, whereas the Barret-Joyner-Halenda (BJH) adsorption and desorption average pore widths were 4.015 and 4.446 nm, respectively. Thus, it was found that rice hull-based activated carbon consisted of mesopores predominantly. These experimental results indicated the potential use of rice hull as a precursor in the activated carbon preparation process with ammonium nitrate. Moreover, the adsorption-desorption isotherm and the adsorption potential of the activated carbon that prepared at the optimum conditions were evaluated.